PRAYER IN THE OLD TESTAMENT AS SPIRITUAL WISDOM FOR TODAY - C Lombaard (Acta Theologica)
The discipline of Biblical Spirituality, with its dual focus on ancient text and modern application, provides the methodological framework for this article. The modern sociological interest in religion, spirituality and prayer is indicated, but not explored, with a shared wisdom orientation in aspects of Old Testament life and in the currently unfolding post-secular religio-cultural climate that forms the bridge between the ancient and the modern in the analysis of prayer. The remainder of this contribution focuses on Deuteronomy 6:4 – the famous Sh’ma prayer – and its historical implications. The editorial history of the book of Deuteronomy, following the theory of E. Otto, forms the basis for understanding more precisely the impact of the Sh’ma in ancient Israel. The link of this prayer to Law inhibited much of its inherent power, testifying to a change in dominant spirituality within post-exilic Judaism. This has had far-reaching implications in the Judeo-Christian history of theology, particularly relating to the grace-law emphases, as indicated in this article, but left to unfold more fully in further research.